Diseño arquitectónico de un centro de exposiciones en el cantón San Pedro de Pelileo - Pillapa Chicaiza, Bryan Santiago (2025)
A cultural facility is far more than just a building; it's a dynamic space where history is breathed, intellect is cultivated, and a community's identity is forged. These spaces, whether they be museums, libraries, theatres, cultural centres or exhibition halls, play a fundamental role in the social, cultural, and economic development of the area in which they are situated. An exhibition centre in the canton of San Pedro de Pelileo would be a facility that would help to disseminate the varied cultural and socioeconomic activities taking place in the canton. Pelileo is a great cultural reference point, and it is also renowned for its growing economic development in the manufacture of jeans. For this reason, an architectural proposal for an exhibition centre in the canton of Pelileo, specifically in the urban parish of Pelileo Grande, is going to be developed. This proposal is based on interviews conducted with individuals involved in the project, ranging from municipal authorities to local residents. A meso and micro-analysis of the area where the proposal is to be developed has also been carried out, with the aim of determining the current state of the land and the urban parish of Pelileo Grande. This analysis has revealed that the proposed location is ideal due to the parish's cultural history and the presence of various recreational facilities. In addition, design strategies have been developed that respond to a SWOT analysis based on the proposal's location.